SVEP1 is a new regulator of arterial tone. (10th June 2022) - Morris, GE; Denniff, MJ; Kostogrys, RB; Bountziouka, V; Rainbow, RD; Samani, NJ; Webb, TR
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Introduction: Vascular tone is regulated by the relative contractile state of vascular smooth muscle cells (VSMCs). Several integrins can directly modulate VSMC contraction by regulating calcium influx through L-type voltage-gated Ca2+ channels (VGCCs). Integrin α9β1 has been identified as preventing exaggerated airway bronchiole contraction. Genetic variants in ITGA9, which encodes the α9 subunit of integrin α9β1, and SVEP1, a ligand for integrin α9β1, are associated with elevated blood pressure, however, neither SVEP1 nor integrin α9β1 have a reported role in vasoregulation. Purpose: To determine whether SVEP1 and integrin α9β1 regulate blood vessel contraction. Methods & Results: Animal experimentation was performed according to ARRIVE (Animal Research: Reporting of In Vivo Experiments) guidelines and "the Principles of laboratory animal care". Immunocytochemical staining showed both ligand and receptor co-localised within the medial layer of the aorta, and in smooth muscle cells in the mesenteric artery. siRNA inhibition of SVEP1 or integrin α9β1 significantly enhanced real-time [Ca2+]i release in isolated human VSMCs to several Gαq/11-vasoconstrictors and to UTP in VSMCs isolated from Svep1+/- mice (Fig. 1A, n=5, P<0.0001). This enhanced cellular contraction was confirmed in blood vessels by wire myography where aortic rings and mesenteric arteries (Fig. 1B, n=10 P<0.0001) from Svep1+/- mice contracted at significantly higher levels than littermate controls. Similar responses were seen in aortic rings when integrin α9β1 was inhibited using the small molecule inhibitor BOP (n=10 P<0.001). Inhibition of VGCCs using nifidepine, or PKC using bisindolylmaleimide (I) prevented this enhanced contraction, suggesting this effect is mediated via VGCCs in a PKC dependent mechanism. Conclusions: Our studies reveal a novel role for SVEP1 and integrin α9β1 in reducing vascular hyper-contractility in response to a range of vasoconstrictor agonists through an L-type voltage gated Ca2+ channel-mediated effect. This regulatory mechanism could suggest a possible explanation for the genetic associations with blood pressure, and provide a new treatment strategy for hypertension.